2000
DOI: 10.1038/76277
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic expression of interferon-γ protects mice from lethal coxsackievirus B3 infection and subsequent myocarditis

Abstract: Cardiovascular disease is one of the leading causes of death worldwide, and has been associated with many environmental risk factors. Recent evidence has indicated the involvement of pathogens such as viruses as causative agents, and specifically identified the coxsackievirus B serogroup as the leading culprit. Not only has coxsackievirus B3 (CB3) been identified from patients with cardiovascular disease, but also infection of mice with CB3 strains can reproduce human clinical heart disease in rodents. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
167
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(179 citation statements)
references
References 20 publications
9
167
2
Order By: Relevance
“…No age-dependent difference in ␣2 mRNA levels was detected in heart tissue. In mice infected with coxsackievirus B3 the immune system both prevents viral replication and exacerbates myocardial damage (26)(27)(28). Age-dependent immune status may be a critical determinant of myocardial disease during EV1 infection of ␣2 and ␣2͞␤1 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…No age-dependent difference in ␣2 mRNA levels was detected in heart tissue. In mice infected with coxsackievirus B3 the immune system both prevents viral replication and exacerbates myocardial damage (26)(27)(28). Age-dependent immune status may be a critical determinant of myocardial disease during EV1 infection of ␣2 and ␣2͞␤1 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…39 In this model, IFN-␥ expression was limited to the pancreas and was not expressed in the heart. 39 The protective mechanism proposed was that viral infection in the heart was subdued, and therefore, myosin was not released from the lysis of infected myocytes and induction of autoimmune heart disease would not occur. Protection was attributed to the antiviral effect of IFN-␥.…”
Section: Influence Of Cytokines On Myocarditis and Th1/ Th2 Immune Rementioning
confidence: 99%
“…In the study of the transgenic animals, viremia was reduced in the heart. 39 Other factors besides reduction of viremia may play a role in protection against viral-induced autoimmune myocarditis. In the study reported herein, in the absence of viral infection but in the presence of immunization with cardiac myosin, IFN-␥ protected against myocarditis presumably by controlling the expression of IL-4 by T cells.…”
Section: Influence Of Cytokines On Myocarditis and Th1/ Th2 Immune Rementioning
confidence: 99%
See 1 more Smart Citation
“…The resulting high-level viremia enables the virus to invade other organs, notably the heart, brain, and liver, and morbidity and mortality are generally the result of damage to these other organs. The pancreatic infection appears to be critical to multiorgan pathogenesis, because when the pancreatic infection is suppressed, mice are protected from consequent myocarditis (4,5). This dependence on a viremic phase for infection of organs makes CVB an appropriate target to evaluate the efficacy of erythrocyte-bound receptor.…”
mentioning
confidence: 99%